Transcriptome analysis reveals the mechanism of fluorine exposure on memory loss of common carp. (October 2020) - Zhang, Yue; Zhang, Peijun; Yu, Peng; Shang, Xinchi; Lu, Yuting; Li, Yuehong
Abstract: Fluorine, an environmental toxicant in our daily life, has been reported to have adverse effects on nervous system. Previous studies demonstrated that fluorine exposure could induce brain injury in fish and human. However, the possible mechanism remains unclear. In the present study, we aimed to reveal the mechanism of fluorine exposure on brain injury of common carp through transcriptome analysis. In the fluorine-exposed carp, 444 brain genes were up-regulated, whereas 742 genes were down-regulated. DNA-templated (regulation of transcription) and multicellular organism development in the GO function annotation accounted for the most biological processes. Nucleus and membrane accounted for the most cellular components and DNA binding and metal ion binding accounted for the most molecular function. Meanwhile, 196 metabolic pathways were identified in Kyoto Encyclopedia of Genes and Genomes (KEGG) Pathway significant enrichment analysis, including long-term depression, Cushing syndrome, nuclear receptors, vascular smooth muscle contraction, Ion channels, and other pathways. Furthermore, we found that the up-regulated and down-regulated trends were similar between the quantitative real-time-PCR and RNA-Seq results, which indicate the transcriptome sequencing data is reliable. In conclusion, our data may provide insights into the mechanisms underlying brain injury induced by fluorine exposure. Graphical abstract: Image 1 Highlights: Fluorine could accumulate in brain tissues and lead to memory loss of common carp. 1186 genes in brain were differentially expressed in the fluorine-exposed carp. Long-term depression and Ion channels were involved in fluorine-induced injury.